Fatigue damage and life evaluation of SS304 and Al 7050-T7541 alloys under various multiaxial strain paths by means of energy-based Fatigue damage models. (July 2016) - Ahmadzadeh, G.R.; Varvani-Farahani, A.
Highlights: Fatigue lives of samples at various variable multiaxial loading paths are assessed. Energy based damage models of Macha, Ellyin and Varvani have been employed. Cycle-counting of Wang-Brown is applied to count reversals over loading spectra. The choice of damage models is discussed based on accuracy in damage assessment. Abstract: Three energy-based models of Macha, Ellyin and Varvani, respectively, are employed to evaluate fatigue life of SS304 and Al 7050-T7451 alloys undergoing variable multiaxial loading spectra. The Macha damage approach assesses the lives based on the equivalent strain energy densities over counted reversals on the critical plane. The Ellyin model evaluates fatigue life data based on the total strain energy density per cycle, consisting of two parts (elastic and plastic strain energies). These energies are quantified from areas within the axial and shear stress-strain hysteresis loops. The Varvani damage approach assesses fatigue lives through summation of the normal and shear energy ranges calculated on the critical plane where the largest stress and strain Mohr's circles over the counted reversals are determined. The reversals over variable multiaxial loading spectra are counted based on the Wang-Brown multiaxial cycle counting method. Damage values are calculated over reversals and then accumulated over a block loading spectrum. The total damage over block histories is then related to fatigue life Nf in the right-hand side of the damage model equations proposed by Macha, Ellyin, and Varvani, respectively. The choice of damage assessment models and how to determine the fatigue life of structural components under variable loading spectra are discussed. Graphical abstract: